Effectiveness of White Galangal Extract (Alpinia galanga W.) AS a Reducer on Formalin of Milkfish Fillets (Chanos chanos F.) - Ariyawati, Shela; Kurnia Hartati, Fadjar; Susilo, Achmadi; Sigit Sucahyo, Bambang; Hariyani, Nunuk (Demeter: Journal of Farming and Agriculture, 2024)
This study aims to determine the effectiveness of white galangal extract (Alpinia galanga W.) as a reducer of formalin levels in milkfish fillets (Chanos chanos F.) with concentrations of 20%, 25%, 30% and soaking times of 30 minutes, 60 minutes. This study uses an experimental method. Data were analyzed using parametric statistics using Analysis of Variant (ANOVA) using Statistic Product and Service Solution (SPSS) version 24. Different concentrations and soaking times of white galangal extract (Alpinia galanga W.) had a very significant effect on reducing formalin levels, increasing protein levels and organoleptic properties of milkfish fillets. Based on the results of the study, L3P2 treatment with a concentration of 30% and a soaking time of 60 minutes was the best treatment in reducing formalin levels with a reduction efficiency of 63,42%, while the protein content of milkfish fillets increased by 17,85%. Organoleptic test results of the appearance of the best milkfish fillets in the L1P1 treatment amounted to 7,72, the best aroma in the L2P1 treatment amounted to 7,56 and the best texture in the L1P1 treatment amounted to 7,56.